2001
DOI: 10.1063/1.1388862
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index change caused by electron irradiation in amorphous As–S and As–Se thin films coated with different metals

Abstract: The refractive index change caused by electron irradiation was measured in amorphous As–S and As–Se thin films coated with different metals. Metal atoms/ions diffused into the films during irradiation. The diffusion was dependent on the metal and influenced the refractive index. The influence was smallest in As40S60 films although these films possessed the highest overall refractive index changes. Au atoms/ions were almost immobile in all films while Ag atoms/ions had the highest mobility. Their high mobility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…The observed measurements, and the calculated optical properties therein, are extraordinary, in the sense that all previously published experiments, with high energy electrons (40 keV), reported an increase in the refractive index between 3% and 8%. [27][28][29][30][31]49 In contrast to the vast literature reporting photon-induced refractive index change, which has yielded as much as an 8% increase in the refractive index of As 2 S 3 film under illumination, 13,15 in our experiment the refractive index decreases as much as 23%. Bearing in mind that the conditions in the cited experiments are significantly different from those reported here, we believe that the discrepancy could be explained by two different mechanisms.…”
Section: Prospective Deduction the Refractive Indexcontrasting
confidence: 89%
See 2 more Smart Citations
“…The observed measurements, and the calculated optical properties therein, are extraordinary, in the sense that all previously published experiments, with high energy electrons (40 keV), reported an increase in the refractive index between 3% and 8%. [27][28][29][30][31]49 In contrast to the vast literature reporting photon-induced refractive index change, which has yielded as much as an 8% increase in the refractive index of As 2 S 3 film under illumination, 13,15 in our experiment the refractive index decreases as much as 23%. Bearing in mind that the conditions in the cited experiments are significantly different from those reported here, we believe that the discrepancy could be explained by two different mechanisms.…”
Section: Prospective Deduction the Refractive Indexcontrasting
confidence: 89%
“…Suhara et al 27 found a maximum change of Dn=n ¼ þ3:6%, with no significant modification in the thickness of the film. On the other hand, Nordman et al [28][29][30] and Tanaka et al 31 independently observed a $3% increment in the refractive index of chalcogenide glass; simultaneously the formation of trenches and mounds, 180 nm and 110 nm, respectively, in chalcogenide films of 5 À 11 lm thick, was observed. They posited that the morphological and optical alteration derives from the structural reorganization and re-bonding of the homopolar and heteropolar bonds, in addition to the electrostatic effects arising from the charge density variation.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These smart optical materials (SOM) change properties based on one of the following properties or effects: Electro-or magneto-absorption changes, [1,2] the Franz-Keldysh effect, [3] the quantum-confined Stark effect, [4] the Zeeman effect, [5] the electrochromic effect, [6] the Pockels effect, [7] the Kerr effect, [8] electro or magneto gyration, [9,10] the electronrefractive effect. [11,12] When an electromagnetic (EM) wave propagates through a medium that has a property of smart optical materials, the wave nature can be altered by an applied field. Such a change may appear as spectral shift of the incident EM wave and/or as a shift in refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…Little attention has been paid to the ternary compound of the type A I B V C VI [12][13][14] including AgSbSe system. Recently, we have published two papers on the studies of Ag 33 Sb 31 Se 36 system [15,16].…”
Section: Introductionmentioning
confidence: 99%